2019
DOI: 10.1155/2019/7506103
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Inducible Nitric Oxide Synthase in Allergic and Nonallergic Nasal Polyp

Abstract: Sinonasal polyps are very common benign lesions of the nasal mucosa. Most of nasal polyps (NP) are idiopathic, and the pathophysiology of this disease is still incompletely understood. Nitric oxide (NO) is a reactive molecule generated by nitric oxide synthase (NOS). NO has been identified as an important mediator in airway function and pathogenesis of several respiratory system diseases. Histological and genetical expression of iNOS was detected to evaluate the role of NO in the pathogenesis of allergic (ANP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
(37 reference statements)
2
4
0
4
Order By: Relevance
“…The mean age in our study was 26.2 years, comparable to studies by Qamar S and Sadek AA where the mean ages were found to be 27±13.4 and 31.6±13.2 7,11 .…”
Section: Discussionsupporting
confidence: 88%
“…The mean age in our study was 26.2 years, comparable to studies by Qamar S and Sadek AA where the mean ages were found to be 27±13.4 and 31.6±13.2 7,11 .…”
Section: Discussionsupporting
confidence: 88%
“…В патофизиологии ПРС роль NO обусловлена как избыточной продукцией нейромедиатора из данных источников, так и присоединением активности индуцибельного фермента (iNOS) в макрофагах. Функция NO в этом случае направлена на модулирование воспалительных процессов, иммунологических реакций и эффективности локального кровотока [12][13][14].…”
Section: Discussionunclassified
“…Мы изучали распределение ряда маркеров, активность которых может определять особенности развития воспалительных процессов (в том числе нейрогенного воспаления) в СО носа, приводящих к формированию, прогрессированию и рецидиву ПРС. Основываясь на морфологической классификации полипозно измененных тканей [1,2,10] и учитывая данные о роли каждого из исследованных факторов в патогенезе пролиферативных и воспалительных заболеваний СО [1,3,14], мы провели детальную характеристику специфики тканевого распределения и активности компонентов нейрокининовой системы (вещество Р и его рецептор NK1), системы синтеза оксида азота (нейрональная и индуцибельная NO-синтаза) и провоспалительного цитокина IL1β в тканях полипа, а также на участках СО пациентов с ПРС.…”
Section: Discussionunclassified
See 2 more Smart Citations